Decolonizing Othello in search of black feminist North American identities: Djanet Sears' Harlem duet and Toni Morrison's Desdemona - Cucarella-Ramon, Vicent (International Journal of English Studies, 2017)
The plays Harlem duet (1997) by African Canadian playwright Djanet Sears and Desdemona (2012) by Toni Morrison signify upon European texts aiming to carve out a new definition of what it means to be black in North America. Therefore both texts make for interesting reading in the study of (black) identity construction within US and Canadian contexts for, by revising Shakespeare’s Othello, they rethink and rewrite a social and racial reality unrelentingly disrupted by difference and hybridity. Sears’ play establishes a specific reading of Canadianness in dialogue with African America to erect a possibility of healing and inclusion, offering a feminist vision of the black self. Similarly, Morrison inscribes the voice of Africa within the US to conclude Sears’ account of a feminist and transnational subjectivity for blacks in North America. By reversing the manly ethos that characterized Shakespeare’s story and bringing the role of women to the front, both plays succeed in readjusting the Shakespearean story to render a feminist, transnational, cosmopolitan and democratic definition of the black female self.